Analysis of tactical thinking in tennis - Thomas, B. N. (University of Stellenbosch, 2011)
The purpose of this study was to explore the knowledge of tennis tactics of a group of South African tennis coaches. A secondary purpose was to gather their perceptions about where they believe they learned about tactics. A mixed methodology approach was used. The first was a quantitative knowledge test administered to 37 coaches. The second was a qualitative semi-structured interview with five coaches. The results of the study showed that there was a significant difference in the choices of tactical options in 43 game scenarios between the less experienced and the more experienced coaches. No differences were found between coaches who were coaching at the top level compared to the lower levels. No differences were found between coaches who had been top tennis players and those who had not. The majority of the coaches in this study reported that they had learned tactics through trial and error. Problems facing the development of top level tennis coaches in South Africa are discussed in relation to their knowledge of tactics and the priorities for the development of mass participation supported by national sport policy.